Assessment of Selfie addiction among undergraduate medical Students - Nath, Som; Kumar, Rajesh; Nath, Manjusha (Indian Journal of Community Health, 2022)
Background: Selfie’ means “A photograph that one has taken of oneself or a self portrait photograph typically taken with a smart phone or digital camera and shared via social media”. Considering the dependency on Internet and selfie taking behavior among professional students, the study was undertaken. Aims and Objective- to determine the demographic profile of selfie users and different variables related to selfie taking and posting and its association with risky dangerous selfie. Material and Methods: A cross-sectional study conducted among 220 undergraduate medical students were using smartphone. Data was collected and analyzed using SPSS version 21. Results: Male students of middle class family of urban areas were more involved in taking selfie. Females were comparatively spending more time (2-3 hrs) on Internet (X2 =19.494 and p = .001).Total 14% students were taking 3-5 selfie and posted on social media(Statistically significant,X2 =7.882,p =0.019). 19(8.63%) participants admitted of taking dangerous selfie of which male 13(14.0%) more than female 06(8.4%). Conclusion: Age and gender affects the number of selfies one clicks. This is developing a new mental disorder ‘selfitis’ as well as desire to take dangerous selfie. There is need of health awareness programme, IEC regarding importance of healthy life style.